2015
DOI: 10.1038/srep15809
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of low dose radiation in response to the oncogenic KRAS induced cellular transformation

Abstract: Recently low dose irradiation has gained attention in the field of radiotherapy. For lack of understanding of the molecular consequences of low dose irradiation, there is much doubt concerning its risks on human beings. In this article, we report that low dose irradiation is capable of blocking the oncogenic KRAS-induced malignant transformation. To address this hypothesis, we showed that low dose irradiation, at doses of 0.1 Gray (Gy); predominantly provide defensive response against oncogenic KRAS -induced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…We have previously shown that LDR have potential to reduce cancer progression at fractionated (1cGyx10) or single doses (0.1Gy or 10cGy) [17, 18]. In accordance, we confirmed that LDR diminishes the growth of 850-5C, BCPAP as well as N-thy ori-3-1 BRAF V600E transformed thyroid cancer cells at both doses (Additional file 1: Figure S1A).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…We have previously shown that LDR have potential to reduce cancer progression at fractionated (1cGyx10) or single doses (0.1Gy or 10cGy) [17, 18]. In accordance, we confirmed that LDR diminishes the growth of 850-5C, BCPAP as well as N-thy ori-3-1 BRAF V600E transformed thyroid cancer cells at both doses (Additional file 1: Figure S1A).…”
Section: Resultssupporting
confidence: 84%
“…The advance of interventional radiology has attracted growing interest in the biological effect of LDR below 0.1Gy doses [16]. From our previous studies, it has become apparent that the LDR has the potential to block KRAS-driven cellular transformation [17] and metastatic cancer progression in breast cancer cells [18]. As, most of the thyroid patients can be cured with surgical treatment together with radioactive iodide, however BRAF-mutated thyroid cancer cells have lower expression of sodium/iodide symporter ( NIS ), thyroid transcription factors ( TTF-1 and TTF-2 ), and thyroglobulin ( TG ) than those cells having wild-type (WT) BRAF [19], and are particularly refractory to radioiodine therapy [20].…”
Section: Introductionmentioning
confidence: 99%
“…This assumption has been confirmed by findings from animal studies which demonstrated that development of experimental tumors may be suppressed by low-dose radiation exposure by stimulation of the removal of preneoplastic cells and/or through prevention of metastasis of already existing cancer. 151 - 154 From these data, it is assumed that doses currently associated with routine diagnostic X-ray procedures (range from 1 to 100 mGy) fall in the “hormetic” zone for high-energy γ-ray photons 155 , 139 and therefore can likely be protective against cancer and several noncancer diseases.…”
Section: Radiation-based Medical Proceduresmentioning
confidence: 99%
“…In our previous work, we showed that LDR reduces the malignant phenotype in oncogene KRAS (Kirsten rat sarcoma viral oncogene homolog) transformed breast epithelial cells. This phenomenon is due to the LDR-induction of antioxidants counteracting KRAS-induced ROS levels in LDR-exposed cells 14 . As metastasis is associated with increased malignant tumor progression, we sought to examine the effects of LDR with regard to EMT in breast cancer cells.…”
mentioning
confidence: 99%